Peculiarities of Organization of Pedagogical Practice for Future Teachers of Primary School in Ukraine and Cyprus: Comparative Analysis - Marios Papaevripidou; Olena Budnyk; Tetyana Blyznyuk; Geogre Olympiou (Vasyl Stefanyk Precarpathian National University, 2022)
The article substantiates the relevance of practice-oriented learning and highlights the importance of practice in school in the process of training future teachers. The authors define progressive ideas of teachers' practical professional training in Ukraine and the Republic of Cyprus. A comparative analysis of the Field Placement Program of student teachers of the two countries was performed. The stages of practice-oriented training of future primary school teachers, the content and results of pedagogical practice are highlighted. The paper describes the experience of the University of Cyprus (UCY) on the activities of clubs in teacher education, where students create conditions to discuss positive and negative situations, share ideas with students at school, carry out collaborative analysis of their teaching during field placement in video clubs. It was found out that in Vasyl Stefanyk Precarpathian National University (PNU) the discussion of the results of students' work during pedagogical practice at school is carried out mostly at the university with a group of teachers and learners where future teachers publicly report on their work. The graduate students' feedback on Teacher Education (results of pedagogical practice in school) is analyzed: the presence of clear instructions on the organization of teacher activities in primary school; ability to set goals and objectives of the lesson; ability to plan professional activities to achieve these goals; skills of organizing educational dialogue in the classroom; ability to create comfortable psychological comfort in the classroom; establishing partnerships with students' parents and teachers at school; skills of communicative culture in teaching children; use of means to stimulate students' motivation, etc.